DIPG-53. CHARACTERIZING THE ROLE OF PPM1D MUTATIONS IN THE PATHOGENESIS OF DIFFUSE INTRINSIC PONTINE GLIOMAS (DIPGS). (4th December 2020) - Khadka, Prasidda; Reitman, Zachary; Lu, Sophie; Buchan, Graham; Hartley, Rachel; Bear, Heather; Georgis, Yoahnna; Jarmale, Spandana; Schoolcraft, Kathleen; Miller, Peter; Gonzalez, Elizabeth; Gionet, Gabrielle; et al.
Abstract: INTRODUCTION: We have previously found that up to 15% of all DIPGs harbor mutations in PPM1D, resulting in the expression of an activated and truncated PPM1D (PPM1Dtr). Here we evaluate the mechanisms through which PPM1Dtr enhances glioma formation and identify its associated therapeutic vulnerabilities. METHODS: We have developed multiple in vitro and in vivo models of PPM1D -mutant DIPGs and applied quantitative proteomic and functional genomic approaches to identify pathways altered by PPM1Dtr and associated dependencies. RESULTS: PPM1D mutations are clonal events that are anti-correlated to TP53 mutations. We find ectopic expression of PPM1Dtr to be sufficient to enhance glioma formation and to be necessary in PPM1D -mutant DIPG cells. In addition, endogenous truncation of PPM1D is sufficient to enhance glioma formation in the presence of mutant H3F3A and PDGFRA . PPM1Dtr overexpression attenuates g-H2AX formation and suppresses apoptosis and cell-cycle arrest in response to radiation treatment. Deep scale phosphoproteomics analyses reveal DNA-damage and cell cycle pathways to be most significantly associated with PPM1Dtr . Furthermore, preliminary analysis of genome-wide loss-of-function CRISPR/Cas9 screens in isogenic GFP and PPM1Dtr overexpressing mouse neural stem cells reveal differential dependency on DNA-damage response genes in the PPM1Dtr overexpressing cells. Consistent with PPM1D 's role in stabilizing MDM2, PPM1D -mutant DIPG models are sensitive to a panel of MDM2 inhibitors (Nutlin-3a, RG7388, and AMG232). CONCLUSION: Our study shows that PPM1Dtr is both an oncogene and a dependency in PPM1D - mutant DIPG, and there are novel therapeutic vulnerabilities associated with PPM1D that may be exploited.